1990
DOI: 10.3382/ps.0690482
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: The Presence of Yersinia enterocolitica and Other Yersinia Species on the Carcasses of Market Broilers

Abstract: Sixty ready-to-cook broiler carcasses obtained from several local supermarkets were tested for the presence of Yersinia enterocolitica and other Yersinia species. In the present study, the authors used two enrichment broths, yeast-extract/rosebengal-bile oxalate sorbose (YER-BOS) and phosphate-buffered saline with a postenrichment KOH treatment (PBS-KOH), and two plating media, cefsulodin-irgasan-novobiocin (CIN) and pectin agar. Yersinia organisms were found on 34 of 60 carcasses (56.7%) and Y. enterocolitica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It is one of a small number of pathogens capable of significant growth at refrigeration temperatures (Swaminathan et al 1982;Walker et al 1990). Pathogenic strains occur widely in food animals, particularly pigs, and have been isolated from both raw and cooked meats worldwide (Hanna et al 1976;Schiemann 1980;Cox et al 1990;De Boer and Nouws 1991;Logue et al 1996). As a consequence, effective methods for the rapid detection and/or enumeration of Y. enterocolitica are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of a small number of pathogens capable of significant growth at refrigeration temperatures (Swaminathan et al 1982;Walker et al 1990). Pathogenic strains occur widely in food animals, particularly pigs, and have been isolated from both raw and cooked meats worldwide (Hanna et al 1976;Schiemann 1980;Cox et al 1990;De Boer and Nouws 1991;Logue et al 1996). As a consequence, effective methods for the rapid detection and/or enumeration of Y. enterocolitica are required.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic strains occur widely in food animals, particularly pigs, and have been isolated from both raw and cooked meats worldwide (Hanna et al . 1976; Schiemann 1980; Cox et al . 1990; De Boer & Nouws 1991; Logue et al .…”
mentioning
confidence: 99%
“…Evidently, the augmented background pressure leads to more active plasmid dissociation among the population of less pathogenic serotypes of Y. enterocolitica (O:9 and O:3) but still preserving their better survivability. Thus, both serotypes seem to have a better adaptive potential resembling other Y. enterocolitica strains in eggs (Ericson and Jenkins, 1992), mussel tissue (Hudson and Avery, 1994), broilers (Bok et al, 1986;Cox et al, 1990), water (Stern and Pierson, 1979), etc. In a different experimental design Goverde et al (1994) reported differences in the growth rates in the plasmid bearing and plasmid cured strains of serotype O:9 in pure culture.…”
Section: Discussionmentioning
confidence: 99%
“…; Iushchenko et al, 1982;Pavlov, 1985;Ding et al, 1986;Schiemann, 1987;De Centorbi et al, 1989;Hamama et al, 1992;Durisin et al, 1997) A wide range of animals: domestic (cat and dog), stock farm (chinchilla, mink, pig, rabbit, cow, goose, horse, sheep, and buffalo), zoo (monkey), wild (raccoon, fox, snail, frog, beaver, deer, ocelot, crab, flies, and fleas), birds (robin), shellfish (oyster), and many species of small rodents (McClure et al, 1971;Wauters et al, 1971;Alonso and Bercovier, 1975;Toma and Deidrick, 1975;Wauters and Janssens, 1976;Kapperud, 1977;Servan et al, 1979;Iushchenko et al, 1982;Gurleva et al, 1985;Kato et al, 1985;Walker and Grimes, 1985;Shayegani et al, 1986;Weber et al, 1987;Cox et al, 1990;Escudero et al, 1991;Weynants et al, 1996;Zheng and Xie, 1996;Funk et al, 1998;Letellier et al, 1999;Naktin and Beavis, 1999) Most of the strains isolated from the environment belong to the nonpathogenic biotype 1A, with the exception of pathogenic strains of biotype 1B, which are frequently isolated from water.…”
Section: Yersinia Enterocoliticamentioning
confidence: 99%